Longitudinal Changes of Plasma ADAMTS13 Activity, Antigen, and Autoantibodies in Patients With Immune-Mediated Thrombotic Thrombocytopenic Purpura. (11th September 2019) - Sui, Jingrui (Jean); Cao, Wenjing; Abdelgawwad, Mohammad; Kocher, Nicole K; Halkidis, Konstantine; Guillory, Bryan K; Williams, Lawrence A; Marques, Marisa B; Zheng, X Long
Abstract: Background: Severe deficiency of plasma ADAMTS13 activity resulting from anti-ADAMTS13 IgG is the primary cause of immune-mediated thrombotic thrombocytopenic purpura (iTTP). Anti-ADAMTS13 IgG may bind and inhibit plasma ADAMTS13 activity and/or accelerate clearance of ADAMTS13 from the circulation. The present study aims to determine the initial and longitudinal changes of plasma ADAMTS13 activity, antigen, and anti-ADAMTS13 IgG and their relationships with clinical responses and outcomes of patients with iTTP after standard treatment. Methods: Thirty-eight patients with a confirmed diagnosis of iTTP who underwent therapeutic plasma exchange (TPE) at UAB Medical Center were enrolled into the study. The study spanned from May 2015 to December 2018. An informed consent was obtained from each participant. Clinical and laboratory information was extracted from the electronic medical record and stored in the Alabama TTP Registry database. Plasma samples were collected prior to the initiation of and every 3 to 5 days after TPE until discharge. Plasma ADAMTS13 activity, antigen, and anti-ADAMTS13 IgG were determined using commercially available reagents. Mann-Whitney test, Fisher's exact test, Spearman rank correlation, Cox proportional hazard regression, and Kaplan-Meier survival analysis were used to determine statistical significances. Results: The median age of this cohort was 46.5 years old; 26 (68%) patients were female and 12 (32%) were male. Twenty-three patients (60%) were experiencing their initial episode while 15 (39%) had an exacerbation/relapse at the time of enrollment. All patients were diagnosed based on the findings of thrombocytopenia, microangiopathic hemolytic anemia, plasma ADAMTS13 activity (<10 U/dL), and inhibitor titer ≥0.4 BU or elevated anti-ADAMTS13 IgG. Following treatment with standard therapy (TPE, corticosteroids, and/or other immunosuppressives), plasma levels of ADAMTS13 activity and antigen increased with a concurrent reduction of anti-ADAMTS13 IgG. However, there were at least three distinct patterns of dynamic changes of these markers over time: (1) rapid increase, (2) slow increase or fluctuation, and (3) persistently low. More interestingly, those with the highest quartile of anti-ADAMTS13 IgG (HR = 4.2) and inhibitor titer ≥1.2 BU (HR = 3.2) at presentation, ADAMTS13 activity <20 U/dL 3 to 7 days during therapy (HR = 2.5), and ADAMTS13 activity <20 U/dL (HR = 3.2) or the lowest quartile of ADAMTS13 antigen at clinical response (HR = 2.8) were all associated with a higher risk of TTP exacerbation (the disease recurred within 30 days following a sustained normalization of platelet counts). Conclusion: Initial and longitudinal assessment of plasma ADAMTS13 activity, antigen, inhibitor titer, and anti-ADAMTS13 IgG may be useful not only for diagnosis but also for predicting the risk of exacerbation. This may influence how we select a therapeutic modality for a better outcome. Long-term follow-up is necessary to determine whether these ADAMTS13 biomarkers at patient discharge are predictive of relapse and mortality.